f(s(a), s(b), x) → f(x, x, x)
g(f(s(x), s(y), z)) → g(f(x, y, z))
cons(x, y) → x
cons(x, y) → y
g(f(s(x0), s(x1), x2))
f(s(a), s(b), x0)
cons(x0, x1)
↳ QTRS
↳ DependencyPairsProof
f(s(a), s(b), x) → f(x, x, x)
g(f(s(x), s(y), z)) → g(f(x, y, z))
cons(x, y) → x
cons(x, y) → y
g(f(s(x0), s(x1), x2))
f(s(a), s(b), x0)
cons(x0, x1)
G(f(s(x), s(y), z)) → G(f(x, y, z))
G(f(s(x), s(y), z)) → F(x, y, z)
F(s(a), s(b), x) → F(x, x, x)
f(s(a), s(b), x) → f(x, x, x)
g(f(s(x), s(y), z)) → g(f(x, y, z))
cons(x, y) → x
cons(x, y) → y
g(f(s(x0), s(x1), x2))
f(s(a), s(b), x0)
cons(x0, x1)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
G(f(s(x), s(y), z)) → G(f(x, y, z))
G(f(s(x), s(y), z)) → F(x, y, z)
F(s(a), s(b), x) → F(x, x, x)
f(s(a), s(b), x) → f(x, x, x)
g(f(s(x), s(y), z)) → g(f(x, y, z))
cons(x, y) → x
cons(x, y) → y
g(f(s(x0), s(x1), x2))
f(s(a), s(b), x0)
cons(x0, x1)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
G(f(s(x), s(y), z)) → G(f(x, y, z))
f(s(a), s(b), x) → f(x, x, x)
g(f(s(x), s(y), z)) → g(f(x, y, z))
cons(x, y) → x
cons(x, y) → y
g(f(s(x0), s(x1), x2))
f(s(a), s(b), x0)
cons(x0, x1)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
G(f(s(x), s(y), z)) → G(f(x, y, z))
f(s(a), s(b), x) → f(x, x, x)
g(f(s(x0), s(x1), x2))
f(s(a), s(b), x0)
cons(x0, x1)
g(f(s(x0), s(x1), x2))
cons(x0, x1)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
G(f(s(x), s(y), z)) → G(f(x, y, z))
f(s(a), s(b), x) → f(x, x, x)
f(s(a), s(b), x0)
G.0(f.1-1-1(s.1(x), s.1(y), z)) → G.0(f.1-1-1(x, y, z))
G.0(f.1-1-0(s.1(x), s.1(y), z)) → G.0(f.1-1-0(x, y, z))
G.0(f.0-0-0(s.0(x), s.0(y), z)) → G.0(f.0-0-0(x, y, z))
G.0(f.1-0-0(s.1(x), s.0(y), z)) → G.0(f.1-0-0(x, y, z))
G.0(f.0-0-1(s.0(x), s.0(y), z)) → G.0(f.0-0-1(x, y, z))
G.0(f.0-1-0(s.0(x), s.1(y), z)) → G.0(f.0-1-0(x, y, z))
G.0(f.0-1-1(s.0(x), s.1(y), z)) → G.0(f.0-1-1(x, y, z))
G.0(f.1-0-1(s.1(x), s.0(y), z)) → G.0(f.1-0-1(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
G.0(f.1-1-1(s.1(x), s.1(y), z)) → G.0(f.1-1-1(x, y, z))
G.0(f.1-1-0(s.1(x), s.1(y), z)) → G.0(f.1-1-0(x, y, z))
G.0(f.0-0-0(s.0(x), s.0(y), z)) → G.0(f.0-0-0(x, y, z))
G.0(f.1-0-0(s.1(x), s.0(y), z)) → G.0(f.1-0-0(x, y, z))
G.0(f.0-0-1(s.0(x), s.0(y), z)) → G.0(f.0-0-1(x, y, z))
G.0(f.0-1-0(s.0(x), s.1(y), z)) → G.0(f.0-1-0(x, y, z))
G.0(f.0-1-1(s.0(x), s.1(y), z)) → G.0(f.0-1-1(x, y, z))
G.0(f.1-0-1(s.1(x), s.0(y), z)) → G.0(f.1-0-1(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
G.0(f.1-1-1(s.1(x), s.1(y), z)) → G.0(f.1-1-1(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
No rules are removed from R.
G.0(f.1-1-1(s.1(x), s.1(y), z)) → G.0(f.1-1-1(x, y, z))
POL(G.0(x1)) = x1
POL(f.1-1-1(x1, x2, x3)) = x1 + x2 + x3
POL(s.1(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
G.0(f.1-1-0(s.1(x), s.1(y), z)) → G.0(f.1-1-0(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
No rules are removed from R.
G.0(f.1-1-0(s.1(x), s.1(y), z)) → G.0(f.1-1-0(x, y, z))
POL(G.0(x1)) = x1
POL(f.1-1-0(x1, x2, x3)) = x1 + x2 + x3
POL(s.1(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
G.0(f.1-0-1(s.1(x), s.0(y), z)) → G.0(f.1-0-1(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
No rules are removed from R.
G.0(f.1-0-1(s.1(x), s.0(y), z)) → G.0(f.1-0-1(x, y, z))
POL(G.0(x1)) = x1
POL(f.1-0-1(x1, x2, x3)) = x1 + x2 + x3
POL(s.0(x1)) = x1
POL(s.1(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
G.0(f.1-0-0(s.1(x), s.0(y), z)) → G.0(f.1-0-0(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
No rules are removed from R.
G.0(f.1-0-0(s.1(x), s.0(y), z)) → G.0(f.1-0-0(x, y, z))
POL(G.0(x1)) = x1
POL(f.1-0-0(x1, x2, x3)) = x1 + x2 + x3
POL(s.0(x1)) = x1
POL(s.1(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDP
↳ QDP
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ QDP
↳ QDP
G.0(f.0-0-1(s.0(x), s.0(y), z)) → G.0(f.0-0-1(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
No rules are removed from R.
G.0(f.0-0-1(s.0(x), s.0(y), z)) → G.0(f.0-0-1(x, y, z))
POL(G.0(x1)) = x1
POL(f.0-0-1(x1, x2, x3)) = x1 + x2 + x3
POL(s.0(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDP
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ QDP
G.0(f.0-0-0(s.0(x), s.0(y), z)) → G.0(f.0-0-0(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
No rules are removed from R.
G.0(f.0-0-0(s.0(x), s.0(y), z)) → G.0(f.0-0-0(x, y, z))
POL(G.0(x1)) = x1
POL(f.0-0-0(x1, x2, x3)) = x1 + x2 + x3
POL(s.0(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ PisEmptyProof
↳ QDP
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDP
G.0(f.0-1-1(s.0(x), s.1(y), z)) → G.0(f.0-1-1(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
G.0(f.0-1-1(s.0(x), s.1(y), z)) → G.0(f.0-1-1(x, y, z))
POL(G.0(x1)) = x1
POL(a.) = 0
POL(b.) = 0
POL(f.0-1-1(x1, x2, x3)) = x2 + x3
POL(f.1-1-1(x1, x2, x3)) = 0
POL(s.0(x1)) = 0
POL(s.1(x1)) = 1 + x1
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
↳ QDP
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDPOrderProof
G.0(f.0-1-0(s.0(x), s.1(y), z)) → G.0(f.0-1-0(x, y, z))
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
G.0(f.0-1-0(s.0(x), s.1(y), z)) → G.0(f.0-1-0(x, y, z))
POL(G.0(x1)) = x1
POL(a.) = 0
POL(b.) = 0
POL(f.0-0-0(x1, x2, x3)) = 0
POL(f.0-1-0(x1, x2, x3)) = x2 + x3
POL(s.0(x1)) = 0
POL(s.1(x1)) = 1 + x1
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QReductionProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
f.0-1-0(s.0(a.), s.1(b.), x) → f.0-0-0(x, x, x)
f.0-1-1(s.0(a.), s.1(b.), x) → f.1-1-1(x, x, x)
f.0-1-0(s.0(a.), s.1(b.), x0)
f.0-1-1(s.0(a.), s.1(b.), x0)